Seroprevalence of HCV markers among HIV infected patients from Curitiba and metropolitan region - Tizzot,Maria Regina (2016)
SUMMARY Objective: to determine the prevalence and epidemiological factors associated with hepatitis (HCV) coinfection in human immunodeficiency virus (HIV) patients from Curitiba and the metropolitan region. Methods: a study with 303 HIV+ patients, mean age 41.2 years (18-73); 50.5% men, followed at the Hospital de Clínicas, Universidade Federal do Paraná, between April 2008 and March 2009. Clinical and epidemiological data were obtained through questionnaires and retrospective analysis of medical records. Anti-HCV antibodies were detected by chemiluminescence immunoassay. Results: a total of 12.9% of HIV+ patients were positive for anti-HCV antibodies, 64.1% were men and 35.9% women, with mean age of 44.5 years (24-66). The frequency of HCV among men was 16.7% and among women 9.1% (p=0.06). HCV prevalence was associated to HIV infection when compared to the general population (p<10-6, OR=100.4; 95CI=13.7-734.9). The parenteral route of transmission was the most frequent among coinfected patients (46.1%), and the sexual transmission among HIV+/HCV- (71.8%) (p=0.02, OR=0.2; 95CI=0.1-0.7). The frequency of intravenous drug users was higher among the coinfected patients (61.5%) compared to the non coinfected (12.6%) (p<10-6, OR=11.1; 95CI=4.5-27.7). Conclusion: the prevalence of coinfection with HCV in HIV+ patients is 12.9%, 88 times higher than in the general population in Curitiba. The most frequent route of transmission in the coinfected patients is parenteral, but the sexual route is also representative (34.6%).